Comparative study of mechanical and physical properties of rice husk filled polyethylene waste composites / Siti Nor Din … [et al.] - Din, Siti Nor; Ahmad Bokhari, Jamilah; Rosni, Nursyarafana; Hashim, Faiezah; Ahmad, Zuliahani (Research Management Institute (RMI), 2023)
Polyethylene (PE), a type of plastic, is utilized extensively in many different applications and has become a significant part of our daily life. However, numerous plastic product manufactures have a significant environmental impact. As a result, several approaches have been investigated in order to reduce waste disposal issues. Rice husk (RH), on the other hand, is a form of agricultural waste that contains lignocellulosic fiber that can be used as a filler in polymer composites. As a result, combining both PE waste and RH fiber could be a viable option for saving our world. The objective of this study was to ascertain the impact of different RH fiber loadings, including 5, 10, 15, 20, and 25 %, on the mechanical and physical characteristics of composites manufactured from used HDPE and LDPE materials. Due to inadequate bonding between the hydrophilic fiber and the hydrophobic polymer matrix, it was discovered that increasing the filler loading lowered the tensile strength, elongation at break, and impact strength of the composites. In comparison to RH/HDPE, the tensile strength of RH/LDPE composites showed greater decline at 45 % at the highest loading of 25 % RH fiber. Both composites showed a 98–99 % decrease in elongation at break as a result of constrained chain elongation and mobility.